До вивчення агрохімічних властивостей едафотопу та щільності популяцій рослин на териконниках Донбасу - Сетт, I.В. (Промышленная ботаника, 2002)
Investigation of some agrochemical properties of edaphotope of the spoil heaps of coal mines in the Donetsk district allowed concluding as for their suitability for plants growth. The most widespread species have been defined, their density being measured. The pronounced connection between density of plant populations on the heaps and edaphotope characteristics has not been revealed.